EFEKTIVITAS MODUL PRAKTIKUM BERBASIS LINGKUNGAN LAHAN BASAH UNTUK MELATIH SIKAP ILMIAH MAHASISWA - Zainuddin, Zainuddin; Mastuang, Mastuang; Misbah, Misbah; Anissa, Rivca (Universitas Tadulako, 2021)
This study aims to determine the understanding of the local people of Sidera regarding the use To fulfil the vision of Lambung Mangkurat University which makes human resources aware of the potential of wetland ligkungan, this research was conducted to describe the effects of wetland environment-based practicum modules for students' scientific training attitudes. This research is a research and development with 4D models (defined, design developed and disseminate) but in this article only effectiveness of practicum module at the stage disseminated. At the dissemination stage, the test bahut is a physics education student FKIP Lambung Mangkurat University and students Tadris Physics UIN Antasari. Scientific attitude data were obtain from the scientific attitudes assessment sheet. As for the indicators of scientific attitudes were curiosity, discovery critical thinking and strong determination. The scientific attitude data obtained was analyzed using the n-gain test. The result of this study where the practicum module is possible for the training of scientific attitudes of students with abilities. It can be concluded that the wetland environment-based practicum module is effective in the course of lectures and scientific attitudes of students.